Top oil temperature prediction at a multiple time scale for power transformers based on adaptive extended Kalman filter - Luo, Yingting; Wang, Lei; Jiang, Junfei; Li, Duanjiao; Lai, Shiyu; Liu, Jianming; La, Yuan; Sun, Wenxing; Shi, Mo (Frontiers in Energy Research, 2024)
To achieve load management optimization and timely failure warning for power transformers, as well as improve the reliability of the power network, this paper proposes a multiple time scale prediction method for top oil temperature (TOT) based on an adaptive extended Kalman filter (AEKF) algorithm. This method combines the Kalman filter (KF) algorithm and the D.Susa thermal model. The TOT, oil exponent and oil time constant are taken as state variables, while the ambient temperature and load current are used as input variables. The iterative optimization of the oil exponent and oil time constant is realized by comparing the estimated and observed TOT values. Moreover, the proposed method utilizes an adaptive noise estimator to correct the noise statistics parameters, which simplifies the initial noise setting and thus further improves the TOT prediction accuracy. A case study is conducted with two 110kV transformers. The results show that comparing the thermal equivalent circuit model and the extended KF algorithm, the proposed method has a higher accuracy in the intraday ultra-short-term prediction on a 15-minute time scale and day-ahead short-term prediction on a 24-hour time scale for the TOT.